PENANDATANGAN AKTA PPAT YANG DILAKUKAN DI LUAR DAERAH KERJA PPAT DI SLEMAN - Dewi P, Caecilia; Sudjito, Sudjito ([Yogyakarta] : Universitas Gadjah Mada, 2011)
T he research aims to understand, why there are many cases of This research is on the signing of PPAT act, that is done outside the PPAT working area Sleman PPAT act being signed outside the work area and to know the legal consequences of signing the act outside the work area of PPAT. uses empirical methods of juridic This research al research, which based on field research. The research aims to obtain primary data, meaning that the facts found in the field associated with other legal rules. To support and complement the data, this research is also juridical normative, by putting the law as a system of building norms. Report of the results from research literature and field research are expected to provide an image or description, which is descriptive qualitative. Descriptive because the results of this research are expected to describe comprehensively and systematically in order answer the proposed problems.